Optimization of coffee oil extraction from spent coffee grounds using four solvents and prototype-scale extraction using circulation process - Somnuk, Krit; Eawlex, Pichai; Prateepchaikul, Gumpon (My University, 2017)
The optimization of two parametersdespresso coffee oil extraction time and the ratio of dried spent coffee grounds (DSCG)-to-solventdwere conducted on DSCG employing four solvents. Extracted yields were investigated using response surface methodology. The two independent variablesdratio of DSCGto- solvent (5.1e24.9 g/g) and extraction time (0.2e39.8 min)dwere optimized in the batch mode. The predicted model was verified using actual experiments. The experimental yields achieved were 14.7 percent by weight (wt%; using hexane), 13.1 wt% (using anhydrous ethanol), 11.8 wt% (using hydrous ethanol), and 7.5 wt% (using methanol). Prototype extraction was tested using a circulation process. Approximately 11.8 wt% oil yield of prototype extraction could be obtained from DSCG under the optimal conditions of 30.4 min extraction time and 22.5 g/g ratio of DSCG-to-hexane from the laboratory-scale results. In this study, the miscella (the solution of coffee oil dissolved in the solvent) from up to six successive extractions was investigated to determine the optimal oil extraction process. The repeated miscella from each successive extraction showed high efficiency and stability of coffee oil yield similar to that obtained using fresh hexane.
Keywords: Circulation process; Coffee oil; Solvent extraction; Spent coffee grounds